Ethnic Constructs in Antiquity The Role of Power and Tradition - Roymans, Nico; Derks, Ton (Amsterdam Archaeological Studies, 2009)
This volume explores the theme of ethnicity and ethnogenesis in societies of the ancient world. Its starting point is the current view in the social and historical sciences of ethnicity as a subjective construct that is shaped through interaction with an ethnic 'other'. The 13 essays collected in this volume are based on the analysis of historical, epigraphic and archaeological source material and thematically range from Archaic Greece to Early Mediaeval Western Europe. Despite frequent claims by ethnic groups to the contrary, all ethnic formations are intrinsically unstable and dynamic over time. Much of this dynamism is to be understood in close association with conflict, violence and changing constellations of power. The explicit theoretical framework, together with the wide range of case-studies makes this volume indispensable for historians, archaeologists and social scientists with an interest in the ancient world.